2022
DOI: 10.3390/ijerph19169833
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Characteristics of Extensor Hallucis Longus Tendon Variations and Its Clinical Implications: A Korean Cadaveric Study

Abstract: The purpose of this study is to ascertain the morphological characteristics of the extensor hallucis longus (EHL) tendon variation using larger-scale dissection of Korean cadavers and to classify the types of variation along with incidence. A total of 158 feet from adult formalin-fixed cadavers (50 males, 29 females) were dissected. The morphological characteristics and measurements of the EHL tendon variants were evaluated. Three types of the EHL tendon variation were classified, wherein the most common type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…By standardizing other surgical variables through the cadaver model, we could directly quantify the differences in angular precision between conventional freehand osteotomies and those conducted using the inclinometer. This controlled comparative testing in cadavers paralleled similar research modalities in orthopedic surgery examining techniques [32][33][34][35]. Our cadaveric protocol and testing methods reinforced the validity and potential generalizability of our findings.…”
Section: Discussionsupporting
confidence: 63%
“…By standardizing other surgical variables through the cadaver model, we could directly quantify the differences in angular precision between conventional freehand osteotomies and those conducted using the inclinometer. This controlled comparative testing in cadavers paralleled similar research modalities in orthopedic surgery examining techniques [32][33][34][35]. Our cadaveric protocol and testing methods reinforced the validity and potential generalizability of our findings.…”
Section: Discussionsupporting
confidence: 63%
“…Many studies are documented to show multiple muscular variations, unilateral, or bilateral, in extensors of foot in cadavers. [6][7][8][9][10][11][12][13][14][15] In the present study, bifurcation of EHL tendon was having medial and lateral slips. Medial slip was the main extensor tendon of great toe, whereas lateral slip was extensor tendon of 2 nd toe.…”
Section: Discussionmentioning
confidence: 87%
“…4 These variations manifest as painful foot on some occasions due to impingement of the surrounding structures. 5 Although various studies have already been conducted representing the variations in extensor tendons of foot, [6][7][8][9][10][11][12][13][14][15] the variations found in our study are rare and have not been previously reported in the literature. Description of tendons in foot is prerequisite for the surgeons to decide for suitable graft in various reconstructive surgeries and for the analysis of injuries in tendons.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation